Hybrid Zn-β-Aminoporphyrin–Carbon Nanotubes - Rebelo, Susana L. H. (2023)
The work was supported through projects UIDB/50006/2020 and UIDP/50006/2020, funded by FCT/MCTES, through national funds. S.L.H.R. (Refs. REQUIMTE/EEC2018/30) and A.M.G.S. thank FCT (Fundação para a Ciência e Tecnologia) for funding through program DL 57/2016—Norma transitória.